2008
DOI: 10.1017/s0029665108005971
|View full text |Cite
|
Sign up to set email alerts
|

Exercise for optimising peak bone mass in women

Abstract: Physical activity is one of the major non-pharmacological methods for increasing and maintaining bone mineral density (BMD) and geometry. As such, it has an important role in maintaining peak bone mass and strength, thus reducing the risk of future osteoporotic fracture. However, not all exercise is effective, so a prescription in terms of optimal type, intensity, frequency and duration is required. Studies using animal models suggest that loading that is high in magnitude, rapidly applied and novel is most ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
54
1
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 65 publications
1
54
1
4
Order By: Relevance
“…Bone mass in aging adults may decrease more rapidly with unfit physical conditions or lifestyle (Karlsson, 2004). Lifelong physical exercise can reduce the rate of bone mineral decline and prevent or delay the onset of osteoporosis (Bailey and Brooke-Wavell, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Bone mass in aging adults may decrease more rapidly with unfit physical conditions or lifestyle (Karlsson, 2004). Lifelong physical exercise can reduce the rate of bone mineral decline and prevent or delay the onset of osteoporosis (Bailey and Brooke-Wavell, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies have considered loading exercises that are high in magnitude, rapidly applied, dynamic and novel as greater osteogenic stimuli, adding that the duration of the workout is less important once a certain threshold level has been reached [13,30,31]. Furthermore, it has been suggested that the distribution of strain may be more important than its magnitude, as unusual patterns of strain can stimulate an osteogenic response at a lower minimum effective strain (MES) [31][32][33]. Mechanical loading, therefore, is more osteogenic when short rest intervals are inserted between cycles in order to avoid the saturation of the bone's adaptive response to mechanical load [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…While high-impact sports are associated with a greater BMD, there is no difference between bone properties of swimmers, who do not experience any loading, compared to the sedentary controls [20,31]. Some studies have also shown the lower prevalence of osteopenia and osteoporosis among those involved in brisk walking compared to those involved in Taijiquan and swimming [5,42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…
Physical activity incorporating impact loading increases bone mineral density, so objective quantification of such activity is needed to quantify adherence to interventions (1) . Accelerometry is a practical method for monitoring daily physical activity that incorporates walking and running (2) but the most-widely-used devices have not been evaluated for their ability to quantify other types of exercise.
…”
mentioning
confidence: 99%